The effects of age and sex on swimming time in master breaststroke swimmers - Knechtle, Beat; Santos Andrade, Marilia; Ahmad, Wais; Moreitz, Sascha; Weiss, Katja; Vancini, Rodrigo Luiz; Nikolaidis, Pantelis Theo; Rosemann, Thomas; Thuany, Mabliny; Seffrin, Aldo (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Purpose. This study investigated the effects of age and sex on swimming performance in master breaststroke swimmers competing in the World Aquatics Master Championships.Methods. For all Master World Championships held between 1986 and 2024, the year of competition, first name, last name, age, age group, stroke and distance were recorded for each swimmer. Descriptive data were presented using mean, standard deviation, and maximum and minimum values. Generalised linear models (GLMs) with a gamma probability distribution and a log-link function assessed the effect of age group and sex on swimming time.Results. Between 1986 and 2024, most swimmers (40.7%) competed in the 50 m event (n = 17,575; 7,911 women and 9,664 men), followed by the 100 m event (35.2%, n = 15,211; 7,158 women and 8,053 men), and the 200 m event (24.0%, n = 10,373; 4,934 women and 5,439 men). The GLM results indicated that sex, age group, and the interaction between sex and age group all had significant effects on the 50, 100, and 200 m races. For 50 m races, the effect of sex was significant ( 2 (1) = 2662.669, p < 0.001), as was the effect of age group ( 2 (13) = 16407.620, p < 0.001), and the interaction between sex and age group ( 2 (13) = 233.234, p < 0.001).Conclusions. The study revealed that men were generally faster than women in all distances and age groups, except for the 90+ age group in the 100 and 200 m events. Future studies could investigate other strokes and distances. Coaches and sports scientists could use these findings to improve the preparation of their master athletes.
Keywords: age; endurance; athlete; master swimmer; performance